Knowledge of HPV-Associated Head and Neck and Oral Cancers Among Health Care Students in Mexico - Urias-Barreras, Cynthia M. (2026)
To assess the knowledge of students in health care-related programs at a public university in Mexico regarding human papillomavirus (HPV) and its association with head and neck and oral cancers. An institution-based descriptive cross-sectional study was conducted using bivariate and multivariate analyses. A representative sample of 323 students completed a questionnaire on sociodemographic characteristics, sexual history, and knowledge of HPV, HPV-related cancers, and the HPV vaccine. Participants were aged 18-36 years; 210 (65.0%) were female and 113 (35.0%) male. Regarding sexual activity, 37.8% had become sexually active at or before age 18, 33.7% thereafter, and 28.5% remained sexually inactive. Over 90% of students were aware that HPV causes cervical cancer, while 63.5% recognized its role in head and neck cancer and 79.5% its association with oral cancer.  Overall, 57.6% had been vaccinated against HPV, and 90.4% were willing to receive the vaccine. Awareness that HPV causes cervical cancer increased recognition of its association with head and neck (OR=6.86, p<0.01; adjOR=5.12, p=0.02) and oral (OR=12.36, p<0.01; adjOR=15.15, p<0.01) cancers. However, willingness to receive the HPV vaccine did not translate into knowledge of HPV’s role in head and neck (OR=0.16, p<0.01; adjOR=0.15, p=0.04) or oral (OR=0.11, p=0.01; adjOR=0.05, p=0.03) cancer. Raising knowledge of HPV’s role in head and neck and oral cancers offers an opportunity to boost vaccination uptake and prevent HPV- related disease.